Study on soil pressure of loose soil in cohesive soil tunnel considering soil arch effect - Dai, Hongtao; Sun, Yang; Rong, Yao; Yu, Junping; Wu, Jiangpeng; Zhang, Yongjun (Frontiers in Earth Science, 2024)
Soil pressure in clay formation tunnels is closely related to soil arch effect and the development of slip surfaces. Firstly, numerical simulation software is used to simulate the actual situation of tunnel excavation, and the change rule of the slip-cracking surface of cohesive soil is analyzed. Secondly, based on the numerical simulation results and the ellipsoid theory, the pressure formula of Terzaghi loose earth is modified considering that the principal stress trace is catenary. Finally, the calculation results are compared with the finite element calculation results to verify the rationality of the formula in this paper. The relationship between the internal friction angle , cohesion force c, eccentricity ε, looseness coefficient β, and the pressure of loose earth is further studied. The results show that there is a gap between the sliding crack angles with or without dilatancy angle and it will affect the development form of soil arch. The slip angle decreases gradually with the increase of the buried depth ratio H/D and becomes stable when the buried depth ratio H/D≥3. Compared with deep-buried tunnels, the increase of internal friction angle in the shallow-buried tunnel is more conducive to reducing the overlying soil pressure. The loose soil pressure decreases with the increase of eccentricity ε and loose coefficient β, and the influence of eccentricity ε on loose soil pressure is significantly greater than that of loose coefficient β. Therefore, the change of eccentricity ε should be paid close attention in the project.